Epistemological Study of Fiqih Lughoh in Arabic Language Learning - Munir, Muhammad Syahrul (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
This article discusses an epistemological study on the examination of Fiqih Lughoh in Arabic language learning. The research focuses on revealing the relationship between epistemological aspects and the teaching of the Arabic language, exploring how linguistic understanding influences the process of Arabic language learning. Through an interdisciplinary approach, this article seeks to comprehend the epistemological implications on the foundation of Arabic language instruction, identify the richness of Arabic language understanding in a linguistic context, and detail effective strategies for integrating Fiqih Lughoh in Arabic language education. There are at least four methodological principles involved, namely al-samā’, al-istishhāb, al-ijmā’, and al-qiyās. The research findings contribute new insights to the development of a more holistic and contextual curriculum, enriching the learning experience of the Arabic language with a profound understanding of the Fiqih Lughoh aspect.